X² + y² = 225
x - 7y = -75
x = 7y - 75
x² + y² = 225
(7y-75)² + y² = 225
(7y - 75)(7y - 75) + y² = 225
49y² - 525y - 525y + 5625 + y² = 225
50y² - 1050y + 5400 = 0
50(y² - 21y + 108) = 0
y² - 21y + 108 ⇒ (y - 12)(y - 9)
x = 7(12) - 75
x = 84 - 75
x = 9 ⇒ (9,12)
x = 7(9) - 75
x = 63 - 75
x = -12 ⇒ (-12,9)
Answer:
numbers
Step-by-step explanation:
Answer:
(-6) - 7 and -6 - (-4)
Step-by-step explanation:
you have to find the rate of change.
this equals -13/4=3.25
Last answer for the first question and in not sure about the second one